Microbiological characteristics and outcomes of children with pleural empyema admitted to a tertiary hospital in southeast China, 2009-2018 - Zhang, Xueya; Zhang, Hailin (The Turkish Journal of Pediatrics, 2021)
Background. Pleural empyema is one of the most serious and life-threatening types of infection in children. The aim of this study was to describe the microbiological characteristics and outcomes of children with pleural empyema. Methods. A retrospective review was conducted of the medical records of 63 children admitted to a tertiary hospital in China with pleural empyema between January 2009 and December 2018. Results. The children had a median age of 1 year (range: 2 months to 16 years) and 33 (52.4%) were female. Bacterial isolates included Staphylococcus aureus (n=15, 23.8%), Streptococcus pneumoniae (n=10, 15.9%), Pseudomonas aeruginosa (n=7, 11.1%), Escherichia coli (n=2, 3.2%), Burkholderia cepacia (n=2, 3.2%), Enterobacter cloacae (n=1, 1.6%), Klebsiella pneumoniae (n=1, 1.6%), and Streptococcus constellation (n=1, 1.6%). All 15 Staphylococcus aureus isolates were found to be resistant to penicillin, and the rate of methicillin-resistant Staphylococcus aureus was high (66.7%,10/15). Overall, 5 of 10 Streptococcus pneumoniae isolates were susceptible to penicillin. Each Staphylococcus aureus and Streptococcus pneumoniae isolate showed susceptibility to vancomycin. Ceftazidime was effective against all Pseudomonas aeruginosa isolates. Of the 63 children, 60 improved, no one died. Conclusions. Staphylococcus aureus and Streptococcus pneumoniae were the leading cause of pleural empyema. Antimicrobial susceptibility testing revealed a high percentage of resistance against penicillin while vancomycin provided 100% coverage for these pathogens. Pseudomonas aeruginosa is the third most common pathogen mainly detected in those under 3 years old in the summer and have shown to be susceptible to ceftazidime. The prognosis is good after appropriate therapy.
Keywords: Pseudomonas aeruginosa; Staphylococcus aureus; Streptococcus pneumonia; children; empyema